2006
DOI: 10.1002/jcc.20465
|View full text |Cite
|
Sign up to set email alerts
|

Electron pairing and chemical bonds: Pair localization in ELF domains from the analysis of domain averaged Fermi holes

Abstract: This article reports the application of a recently proposed formalism of domain averaged Fermi holes to the problem of the localization of electron pairs in electron localization function (ELF) domains and its possible implications for the electron pair model of chemical bond. The main focus was on the systems, such as H 2 O or N 2 , in which the ''unphysical'' population of ELF domains makes the parallel between these domains and chemical bond questionable. On the basis of the results of the Fermi-hole analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 41 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…[47] Ponec and Chaves have addressed this problem by analyzing domain-averaged Fermi holes. [52] They concluded that the explanation lies in the determination of basin boundaries, and contamination by electrons in neighboring domains.…”
Section: Defining the Lone Pair Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] Ponec and Chaves have addressed this problem by analyzing domain-averaged Fermi holes. [52] They concluded that the explanation lies in the determination of basin boundaries, and contamination by electrons in neighboring domains.…”
Section: Defining the Lone Pair Domainmentioning
confidence: 99%
“…one electron) in a non-infinitesimal volume of space (e.g. [52] They concluded that the explanation lies in the determination of basin boundaries, and contamination by electrons in neighboring domains. This is because many electrons contribute to the average population.…”
Section: Introductionmentioning
confidence: 99%
“…N 2 is a textbook example for the triple bond. Nevertheless, the topological analysis of the ELF gives a population close to four electrons in the NN bond, which does not correspond to the common Lewis structure17. Here, we searched for the domains maximizing the probabilities of finding three up and three down electrons between the two nuclei, following the traditional σ/π interpretation of the bond.…”
Section: Applicationsmentioning
confidence: 99%
“…The ELF population analysis often yields basin populations close to the integer values expected from the Lewis model; however the deviations from even integers have been interpreted by some authors as a deficiency of the partition scheme [64,65]. In the mesomery model, the charge distribution is represented by a superposition of weighted structures, the ELF populations and population covariances enable therefore to estimate the weights of the considered structures [66,67]; moreover the electron number probabilities provide additional pieces of information about the electron delocalization.…”
Section: The Elf Population Analysismentioning
confidence: 97%